2002
DOI: 10.1006/mthe.2002.0647
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinating Virus of Japan (HVJ) Envelope Vector as a Versatile Gene Delivery System

Abstract: We have developed a simple method for converting the lipid envelope of an inactivated virus to a gene transfer vector. Hemagglutinating virus of Japan (HVJ; Sendai virus) envelope vector was constructed by incorporating plasmid DNA into inactivated HVJ particles. This HVJ envelope vector introduced plasmid DNA efficiently and rapidly into various cell lines, including cancer cells and several types of primary cell culture. Efficiency of gene transfer was greatly enhanced by protamine sulfate and centrifugation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
224
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(227 citation statements)
references
References 44 publications
2
224
1
Order By: Relevance
“…It has been reported that a highly effective HVJ-liposome gene transfer technique introduced decoy ODN mainly into renal interstitial fibroblasts. 40 Together with the present results, this suggests that this strategy specifically suppresses Sp1-mediated transcription in the interstitial areas of the targeted kidney, and thus can be used as an effective therapy for tubulointerstitial fibrosis caused in nephritic diseases.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It has been reported that a highly effective HVJ-liposome gene transfer technique introduced decoy ODN mainly into renal interstitial fibroblasts. 40 Together with the present results, this suggests that this strategy specifically suppresses Sp1-mediated transcription in the interstitial areas of the targeted kidney, and thus can be used as an effective therapy for tubulointerstitial fibrosis caused in nephritic diseases.…”
Section: Discussionsupporting
confidence: 82%
“…40 Briefly, egg yolk phosphatidylcholine (Sigma), dioleolyphosphatidylethanolamine (Avanti Polar Lipid, Birmingham, AL, USA), egg yolk sphingomyelin (Sigma), bovine brain phosphatidylserine (Sigma), and cholesterol (Sigma) were mixed in a molar ratio of 16. …”
Section: Preparation Of Hemaggluting Virus Of Japan (Hvj) Liposomementioning
confidence: 99%
“…The subcutaneous injection of STAT6 decoy ODN with HVJ-E after sensitization exhibited a significant inhibitory effect on both STAT6 binding to nucleus and the late-phase response in line with Kaneda's report. 27 A histopathological analysis revealed a tremendous reduction in both the infiltration of eosinophils, mast cells, and especially mast cell degradation in single or repeated challenged skin in STAT6 decoy ODN-transfected mice. STAT6 signaling is essential for the hapten-induced increase in Th2 cytokines production in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…27 The virus was inactivated by b-propiolactone (0.0075-0.001%) treatment or by UV irradiation. In both cases, the virus preparation lost the ability to replicate.…”
Section: Preparation Of the Hvj-e Vectormentioning
confidence: 99%
See 1 more Smart Citation